2000
DOI: 10.1093/oxfordjournals.bja.a013582
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section for placenta praevia: a retrospective study of anaesthetic management

Abstract: A retrospective survey of anaesthesia for Caesarean section (CS) for placenta praevia was performed, covering the period between January 1, 1984 and December 31, 1998. Three hundred and fifty consecutive cases of placenta praevia were identified. Overall a regional technique was used 60% of the time. Five women had a placenta accreta which required Caesarean hysterectomy: one had general anaesthesia (GA) throughout and four initially received a single-shot spinal injection. Of these latter four cases, two were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 2 publications
5
43
0
Order By: Relevance
“…Regional or General anesthesia can be used for the anesthetic management of such patients, 14 both techniques having advantages as well as disadvantages. Regional anesthesia may be associated with decreased blood loss, decrease necessity for hysterectomy to control maternal hemorrhage and improved fetal outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional or General anesthesia can be used for the anesthetic management of such patients, 14 both techniques having advantages as well as disadvantages. Regional anesthesia may be associated with decreased blood loss, decrease necessity for hysterectomy to control maternal hemorrhage and improved fetal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…14,16 This is mainly due to increase sympathetic tone and increased arterial blood pressure leading to increased blood loss. However, if there is active bleeding or the patient is unstable, general anesthesia is the choice for maintaining airway, breathing and circulation 17,18 and if there is no active bleeding and the patients is hemodynamically stable regional anesthesia is the choice.…”
Section: Discussionmentioning
confidence: 99%
“…Arcario et al suggested that regional anesthesia is not contraindicated even in cases of simple placenta accreta [10]. Parekh et al in a retrospective review also revealed that regional anesthesia was used in 60% of cases [5]. Combined spinal epidural anesthesia has also been suggested as anesthetic technique for placenta previa [11].…”
Section: Discussionmentioning
confidence: 99%
“…General anesthesia is believed to be preferable for this group of patients [4]. There is also evidence that a majority of anesthesiologists consider using regional anesthesia for placenta previa [4][5][6].…”
mentioning
confidence: 99%
“…[40] Two retrospective studies conclude that regional anesthesia is safe, [41,42] and one small randomized trial suggests that epidural anesthesia is superior to general anesthesia with regard to maternal hemodynamics. [43] When prolonged surgery is anticipated in women with prenatally diagnosed placenta accreta, general anesthesia may be preferable, and regional analgesia could be converted to general anesthesia if undiagnosed accreta is encountered [41].…”
Section: Methods Of Anesthesia For Cesarean Sectionmentioning
confidence: 99%